Doppervelocimetria da artéria oftálmica nas formas precoce e tardia da pré-eclâmpsia - Silva Netto, José Paulo da [UNESP] (2015)
Introduction: Preeclampsia contributes considerably to increased maternal and perinatal morbidity and mortality. This disease can be classified into early and late onset preeclampsia, according to the timing of their clinical manifestations appearance. The ophthalmic artery Doppler is an objective method that can facilitate the diagnosis of hypertension during pregnancy, identifying its different manifestations. Objective: Differentiate through the Doppler of the ophthalmic artery the hemodynamic pattern of the ophthalmic artery of early and late onset preeclampsia. Methods: Cross-sectional study of 67 pregnant women with early preeclampsia and 93 pregnant women with late preeclampsia performed in the third trimester of pregnancy. All women had performed the right ophthalmic artery Doppler that evaluated the following parameters for the quantification wave flow rate: resistance index (RI), pulsatility index (PI), peak systolic velocity (PSV), peak diastolic velocity (PVD), end-diastolic velocity (EDV) and peak velocity ratio (RPV). The results were subjected to statistical analysis, considering significant when p <0.05. Results: The mean Doppler indices of early and late onset preeclampsia were: RI = 0.7 ± 0.1 vs 0.7 ± 0.1, IP= 1.3 ± 0.4 vs 1.4 ± 1.1, PVS: 33.2 ± 8.2 vs 34.3 ± 10.0, PVD: 26.5 ± 8.1 vs 25.5 ± 9.4, VDF: 11.2 ± 3.8 vs 11.7 ± 4.6 and RPV: 0.8 ± 0.2 vs 0.7 ± 0.2. The speed of peak ratio was significantly higher in patients with early preeclampsia. There was no significant difference in terms of resistance index values, pulsatility index, peak systolic velocity, peak diastolic velocity and end diastolic velocity. Conclusion: The Doppler of the ophthalmic artery is a test that can be used in the evaluation of pregnant women with preeclampsia, showing difference in quantitative indices such as peak velocity ratio when comparing women with early and late onset preeclampsia